Evidence-based inpatient postnatal care among women in a national hospital in Kazakhstan: a best practice implementation project. Issue 3 (9th September 2020) - Colet, Paolo; Aimagambetova, Gulzhanat; Kossybayeva, Kapiza
ABSTRACT: Objective: The current project generally aims to assess compliance with evidence-based criteria regarding postnatal care among women in a national hospital in Kazakhstan. Introduction: Improvements in reducing maternal and infant mortality in Kazakhstan have been noted over the past 2 decades. However, recent studies have indicated that care given to women during the perinatal period, which includes the postnatal period, is unsatisfactory. In addition, service delivery remains unstandardized, while outdated and inconsistent application of practice guidelines are observed in the clinical setting. Methods: Following the JBI Practical Application of Clinical Evidence System and Getting Research into Practice audit and feedback tool with three phases of activities, this project utilizes an implementation framework that incorporates quality improvement. Also, the audit tool consists of seven criteria to assess compliance with evidence-based postnatal care. Results: Results indicate varying levels of compliance with the seven criteria used in this project. Criteria 1 and 7, which document postnatal plan and psychological assessment, garner the highest compliance at 100% in baseline and follow-up data collection. The compliance rate on criterion 4, which discusses the prevention of sudden infant death syndrome, decreases from 64% on the baseline to 29% on the follow-up. Similarly, criterion 6, which provides information about bottle feeding, exhibits further decrease with compliance from 43 to 40%. Importantly, increased compliance was noted on criterion 5, which is about breastfeeding, from 58 to 95% from the baseline and follow-up audit. Conclusion: The current study successfully implements evidence-based inpatient postnatal care in Kazakhstan and reveals varying results on compliance and the increasing knowledge of nurses and midwives on evidence-based postnatal care.